EVALUACIÓN PRESUPUESTARIA DEL GOBIERNO AUTÓNOMO DESCENTRALIZADO PARROQUIAL DE BELLAVISTA DEL CANTÓN ESPÍNDOLA PERIODO 2017 - Jaramillo Jaramillo, Stalin Ismael (2019)
The budgetary evaluation is the phase of the budgetary cycle in which the executing institution measures the effectiveness and efficiency of the results achieved. In the parish GAD of Bellavista of the Espindola Canton, at the time of making the budget the projects and programs prioritized in the PDyOT are not considered in their totality, which is the main guideline to follow to fulfill the objectives and goals proposed by the parish, it does not apply budgetary or management indicators, there is low citizen participation in relation to the management it performs. With the purpose of fulfilling the objectives of the thesis work, we proceeded to compile information such as: Annual Operative Plan, state of budgetary execution, report of accountability, initial budget and the budgetary cédulas of income and expenses of the entity period 2017. A coherence analysis was carried out between the GAD budget and the Development and Territorial Order Plan, in which it was verified that 100% of this instrument is not taken into account at the time the budget is made. Likewise, a horizontal analysis of the state of budget execution was carried out in order to see the deviations it has had and apply indicators and determine the level of fulfillment of the established goals. Likewise, budget management indicators were applied in what was determined to depend mostly on the transfers received from the Central Government, in compliance with the Annual Operative Plan, it was obtained that out of 16 projects included in the POA, only 5 were executed, resulting in 31% of project execution, and finally indicators of citizen participation were applied based on the survey applied to citizens, from which 58.67% of participation was obtained.